Educational Terminology in the Al-Quran Perspective - Peri Gunawan (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
This study aims to examine and examine more deeply the educational terms contained in the Qur'an. This research uses a descriptive philosophical method, namely explaining something, especially academic terminology in the Qur'an, in more depth. The problem studied in this study is the verification of educational terms contained in the Qur'an. Therefore, this study uses an inductive mindset. The data and facts of this study are observed empirically, then processed, compiled, analyzed, and deduced, which are general. Explain the term education in the Qur'an philosophically, using a content study approach. The type of data in this study is Secondary Data; related to the method of interpreting the Qur'an on educational verses, researchers use the maudhu'I interpretation method. There are several terms of education in the Qur'an, namely ta’lim, tadris, ta’dib, and tazkiyah. The erm ta'lim emphasizes more aspects of good knowledge delivery, understanding, understanding and responsibility, as well as cultivating trust in students. The term ta'dib emphasizes mastering the correct knowledge in a person so that he is expected to be able to do good behaviour. Term tadris more on trying to prepare students not only in terms of reading but also in their application of moral and spiritual values. While the term tazkiyah becomes the role value and ultimate goal in Islamic Education, meaning that it is the ultimate goal of Islamic Education, namely the purification of the soul to get the blessings and joy of Allah Swt. Everything is interrelated in content but different in terms of emphasising its meaning.